A review on the occurrence, distribution, characteristics, and analysis methods of microplastic pollution in ecosystem s. Issue 1 (1st January 2021) - Chen, Jiaxin; Wang, Weimu; Liu, Hui; Xu, Xiaohui; Xia, Jihong
ABSTRACT: Although plastic materials play an essential role in life, the intensive production of plastic products and mismanagement of plastic waste worldwide have resulted in microplastic pollution. The two major characteristics of environmental microplastics are having small size and resistance to degradation, which make microplastics a persistent organic pollutant. As microplastic pollution has been observed in diverse environmental matrices, it has attracted great attention of scholars globally. Over the last decade, scholars have mainly documented the particle properties of microplastics, such as size, shape or color and their adverse effects on organisms. However, no research has updated on environmental microplastics from the perspective of multi-media. Our review first summarized the literature in the occurrence, distribution, and characteristics of microplastics in three kinds of environmental matrices (water, soil, and air) to the public. We then identify the methodological challenges in researches and discuss the advantages and limitations of popular methods to analyze environmental microplastics. Eventually, our paper highlights the current challenges and proposes suggestions for the future research on microplastic pollution.